Multi-machine analysis of termination scenarios with comparison to simulations of controlled shutdown of ITER discharges. (22nd December 2017) - de Vries, P.C.; Luce, T.C.; Bae, Y.S.; Gerhardt, S.; Gong, X.; Gribov, Y.; Humphreys, D.; Kavin, A.; Khayrutdinov, R.R.; Kessel, C.; Kim, S.H.; Loarte, A.; et al.
Abstract: To improve our understanding of the dynamics and control of ITER terminations, a study has been carried out on data from existing tokamaks. The aim of this joint analysis is to compare the assumptions for ITER terminations with the present experience basis. The study examined the parameter ranges in which present day devices operated during their terminations, as well as the dynamics of these parameters. The analysis of a database, built using a selected set of experimental termination cases, showed that, the H-mode density decays slower than the plasma current ramp-down. The consequential increase in f GW limits the duration of the H-mode phase or result in disruptions. The lower temperatures after the drop out of H-mode will allow the plasma internal inductance to increase. But vertical stability control remains manageable in ITER at high internal inductance when accompanied by a strong elongation reduction. This will result in ITER terminations remaining longer at low q ( q 95 3) than most present-day devices during the current ramp-down. A fast power ramp-down leads to a larger change in β p at the H–L transition, but the experimental data showed that these are manageable for the ITER radial position control. The analysis of JET data shows that radiation and impurity levels significantly alter the H–L transition dynamics. Self-consistent calculations of the impurity content and resulting radiation should be taken into account when modelling ITER termination scenarios. The results from this analysis can be used to better prescribe the inputs for the detailed modelling and preparation of ITER termination scenarios.